The globaljetwatch spectrographs: A fibre-fed spectrograph for small telescopes - Clarke, F; Gosling, A; Doolin, S; Goodall, P; Perez, S; Pattinson, P; Makin, R; Blundell, K (2008)
The GlobalJetWatch project (www.globaljetwatch.net) will place small (0.5-metre) commerical telescopes in four schools around the world. Each telescope will be equipped with a custom designed spectrograph, currently being built by the Astrophysics sub-department of the University of Oxford. The scientific goal of the project is to provide continual monitoring of a rosetta stone object, the micro-quasar SS433. In addition,the project has a significant out-reach element, aiming to involve school children on four-continents in front-line astronomical research. The spectrograph is a fibre-fed fixed format cross-dispersed echellete design providing R 6000 spectra from 4300-8500Å in a single exposure. The spectrograph is built almost entirely from off-the-shelf components. The four GlobalJetWatch sites (Australia, India, South Africa,Chile) will be commissioned in 2008/09. Here we present the baseline design of the spectrograph, and initial results from the prototype on-sky commissioning in Oxford.